ANALISIS KECERDASAN INTERPERSONAL PENGASUH DI TAMAN PENITIPAN ANAK SE-KECAMATAN TAMPAN KOTA PEKANBARU - Rizka Syahfitri; Wusono Indarto; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstarck: This research aims to describe the Interpersonal Intelligence Caregivers in the nursery in Tampan sub-district Pekanbaru. Population and sample in this research are 45 caregivers who were in the day care in Tampan sub-district Pekanbaru.The data collection techniques that use a questionnaire with a model statement. The data analysis using the percentage formula. Indicators of social sensitivity at 84.62% was obtained from 45 caregivers in the day care, while that of indicators Social Insight percentage values obtained 84.37% of the 45 caregivers in the day care in Tampan sub-district Pekanbaru.Thus it can be concluded that the over all percentage indicator on the analysis of interpersonal intelligence caregivers in the day care in Tampan sub-district Pekanbaru has a percentage of 85.65% which is classified in the category of "High", because it is in the category ratings between 81-100% were categorized as "High". It can be concluded that interpersonal intelligence caregivers in the day care in Tampan subdistrict Pekanbaru are "High".Key Words: Caregivers , interpersonal intelegence